2022
DOI: 10.3389/fevo.2022.992389
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic patterns in African wild dogs reveal signs of effective dispersal across southern Africa

Abstract: Across much of Africa, decades of civil war, land reforms, and persecution by humans have decimated wildlife populations. African wild dogs (Lycaon pictus) have declined dramatically during the past decades, but have shown recent natural recolonisation of some areas. In Angola, they were rediscovered after almost five decades when no surveys were being conducted, and they have recolonised areas in southern Zimbabwe and northern South Africa. Wild dogs were also reintroduced to Mozambique, where only few indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…(2012) revealed that dispersal and the associated mortality indeed led to a decline in genetic diversity and, subsequently, to a net loss of individuals. At present, our own study population appears to benefit from moderate levels of dispersal, as an analysis across Southern Africa revealed a genetically healthy cluster in the Kavango‐Zambezi Transfrontier Conservation Area (Tensen et al., 2022). This cluster may, however, be at risk depending on future flood conditions.…”
Section: Discussionmentioning
confidence: 77%
“…(2012) revealed that dispersal and the associated mortality indeed led to a decline in genetic diversity and, subsequently, to a net loss of individuals. At present, our own study population appears to benefit from moderate levels of dispersal, as an analysis across Southern Africa revealed a genetically healthy cluster in the Kavango‐Zambezi Transfrontier Conservation Area (Tensen et al., 2022). This cluster may, however, be at risk depending on future flood conditions.…”
Section: Discussionmentioning
confidence: 77%